Pengalaman Keluarga Merawat Pasien Halusinasi Pendengaran di Rumah Sakit Jiwa Jambi - Vevi Suryenti Putri; Mustikasari Mustikasari; Renidayati Renidayati (Universitas Batanghari Jambi, 2019)
The purpose of this study was to determine the experience of families caring for auditory hallucinations in Jambi Mental Hospital. This type of research is a qualitative research with a descriptive phenomenological study. Participants in this study were nuclear family members who cared for their families suffering from auditory hallucinations that had been selected according to predetermined criteria, totaling 7 participants. The sampling method was purposive sampling with Colaizzi method data analysis. Test data using credibility with member check, transferability, dependability, confirmation. The study obtained the results of four themes, namely: 1) Types of family care at home, 2) Findings of families in caring, 3) Types of problem solving in families 4) Services received